MEDIASI PROGRAM KOLABORASI DINAS KEHUTANAN PROVINSI KALIMATAN SELATAN DENGAN PEMERINTAH DESA TANAH INTAN DALAM PENGEMBANGAN POTENSI AGROWISATA KEBUN BUAH - Fadly; Noviana Sari; Khairina; Noor Helmah; Lenny Amelia; Noor Citra Rosalinda; Dwi Carolina A; Muhammad Nor ikhsan; Muhammad Rifki Fauzi (Wadah Inovasi Indonesia, 2022)
The flood disaster that occurred in early 2021 due to very high rainfall intensity resulted in several areas in South Kalimantan experiencing disasters, namely floods. The disaster destroyed several public facilities and caused huge losses to the people of South Kalimantan. This also resulted in many trees dying due to water that was too deep, conditions like this really needed a collaborative program between the DISHUT of KAL-SEL Province and the village government to further develop areas affected by flooding and rebuild the potentials that are closely related to plants. , such as citrus plantations, rubber and other plantations. This program aims to enable flood-affected areas to do reforestation for villages that are devoid of green trees.